Five-hole corrugated pipe and production device - ZHANG TAOTAO; LIU SONGXI (2024)
The utility model discloses a five-hole corrugated pipe and a production device, the production device is used for producing the five-hole corrugated pipe, the five-hole corrugated pipe comprises a five-hole pipe and a corrugated pipe, and the five-hole pipe is located in the corrugated pipe. Due to the fact that the five-hole pipe is located in the corrugated pipe, the corrugated pipe has high strength and can bear high pressure, the five-hole pipe is well protected, the structure of the five-hole pipe is stable, and the service life of the five-hole pipe is prolonged. 本实用新型公开了一种五孔波纹管及生产装置，生产装置用于生产五孔波纹管，五孔波纹管包括：五孔管和波纹管，五孔管位于所述波纹管内。由于五孔管位于波纹管内，波纹管具有较高的强度，能承受较高的压力，使五孔管得到良好的保护，五孔管结构稳定，延长了五孔管的使用寿命。